Whistle characteristics of Indo-Pacific bottlenose dolphins (Tursiops aduncus) in the Fremantle Inner Harbour, Western Australia - Ward, R.; Parnum, Iain; Erbe, Christine; Salgado Kent, Chandra (Australian Acoustical Society, 2016)
Bottlenose dolphins use whistles to communicate with their conspecifics and maintain group cohesion. We recorded 477 whistles of Indo-Pacific bottlenose dolphins (Tursiops aduncus) in the Fremantle Inner Harbour, Western Australia, on nine occasions over a six-week period during May/June 2013. Over half (57 %) of the whistles had complex contours exhibiting at least one local extremum, while 32 % were straight upsweeps, 5 % downsweeps and 6 % constant-frequency. About 60 % of whistles occurred in trains. Fundamental frequency ranged from 1.1 to 18.4 kHz and whistle duration from 0.05 to 1.15 s. The maximum numbers of local extrema and inflection points were 7 and 9, respectively. Whistle parameters compared well to those of measurements made from other T. aduncus populations around Australia. Observed differences might be due to ambient noise rather than geographic separation.